2021
DOI: 10.1080/03323315.2021.1916559
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ use of technology and the impact of Covid-19

Abstract: Teaching online poses challenges for teachers trained primarily to work face to face. The Covid-19 pandemic and subsequent lockdown of schools has forced teachers to move online to ensure students continue their studies. This is not an easy transition and success depends on educators having the skills, knowledge, and competencies for online teaching. As part of the Adaptive and Inclusive Learning Environment (AILE) project, this study surveyed 38 primary and post-primary teachers in Ireland on their use of tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
111
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 14 publications
7
111
1
6
Order By: Relevance
“…It was clear from teachers’ responses that they understood the precarious conditions that families, especially low-income families, faced during the pandemic. Students’ lack of access to a computer during the pandemic has been reported by researchers in both developing and developed countries (Winter et al, 2021 ). For example, 21% of parents in the Pew research Center ( 2020 ) poll in the U.S. shared that their children did not have access to a computer at home, 22% revealed that the home did not have a reliable internet connection, and 20% shared that their children most probably would use a cell phone to complete their schoolwork.…”
Section: Discussionmentioning
confidence: 95%
“…It was clear from teachers’ responses that they understood the precarious conditions that families, especially low-income families, faced during the pandemic. Students’ lack of access to a computer during the pandemic has been reported by researchers in both developing and developed countries (Winter et al, 2021 ). For example, 21% of parents in the Pew research Center ( 2020 ) poll in the U.S. shared that their children did not have access to a computer at home, 22% revealed that the home did not have a reliable internet connection, and 20% shared that their children most probably would use a cell phone to complete their schoolwork.…”
Section: Discussionmentioning
confidence: 95%
“…Since the baseline measurements were assessed in 2018 and the follow-up period in the register was in 2020, just before the onset of the COVID-19 pandemic, the present study does not allow to estimate how the pandemic might have affected the association between the implementation of new technology and work participation. It is well known, however, that the COVID-19 crisis is having a drastic impact on new technology, work, and employment [ 50 , 51 , 52 , 53 , 54 ]. The pandemic-imposed lockdown has affected all industries and service sectors alike, including health care, manufacturing, and office work, among others, and has elevated the role of technology in the workplace [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transition from the old to new educational modality has not been an task. Its success, according to Winter, Costello, O'Brien, and Hickey (2021) depends on educators having the knowledge and skills for remote teaching. However, in the lack of time for professional development activities to capacitate the teachers, self-learning was an inevitable enabler.…”
Section: Discussionmentioning
confidence: 99%